2000
DOI: 10.1176/appi.ajp.157.9.1520
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Regional Cerebral Blood Flow Patterns in Anorexia Nervosa Patients With Binge/Purge Behavior

Abstract: Specific activation in cortical regions suggests an association between habitual binge/purge behavior and the food recognition process linked to anxiety in patients with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 8 publications
1
27
0
1
Order By: Relevance
“…As described above, previous brain imaging studies have shown pictures of food to emaciated and malnourished AN individuals. These studies found altered activity not only in the insula and OFC, but in broad regions including mesial temporal, parietal, and the anterior cingulate cortex when ill AN subjects were compared to controls (122,(125)(126)(127)129,197).…”
Section: Feeding Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…As described above, previous brain imaging studies have shown pictures of food to emaciated and malnourished AN individuals. These studies found altered activity not only in the insula and OFC, but in broad regions including mesial temporal, parietal, and the anterior cingulate cortex when ill AN subjects were compared to controls (122,(125)(126)(127)129,197).…”
Section: Feeding Behaviormentioning
confidence: 97%
“…When emaciated and malnourished AN individuals are shown pictures of food, they display abnormal activity in the insula and orbitofrontal cortex (OFC) as well as in mesial temporal, parietal, and the anterior cingulate cortex (122)(123)(124)(125)(126)(127). Studies using SPECT, PET-O15, or fMRI, found that when subjects ill with AN ate food, or were exposed to food, they had activated temporal regions, and often increased anxiety (122,(124)(125)(126). Those results could be consistent with anxiety provocation and related amygdala activation, and the notion that the emotional value of an experience is stored in the amygdale (128).…”
Section: Appetitive Regulationmentioning
confidence: 99%
“…Furthermore, brain imaging has been performed in conjunction with paradigms and tasks that are meant to elicit areas of brain activation that might be specific to AN pathophysiology [12] . Most paradigms are based on 2 integral parts of AN pathophysiology: weight phobia [13][14][15][16] and body image distortion [17][18][19][20] . Among these studies, imaging modalities and tasks are not consistent, and some patient groups are small.…”
Section: Influence Of Satiety and Subjective Valence Rating On Cerebrmentioning
confidence: 99%
“…Previous brain imaging studies have shown pictures of food to emaciated and malnourished AN individuals. These studies found altered activity not only in the insula and OFC, but in broad regions including mesial temporal, parietal, and the anterior cingulate cortex when ill AN subjects were compared to controls (Nozoe et al, 1993;Ellison et al, 1998;Naruo et al, 2000;Gordon et al, 2001;Uher et al, 2004). In addition, one study used pictures of food and functional magnetic resonance imaging (fMRI) to study individuals who were recovered from AN (Uher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%